A qualitative exploration of stressors and coping strategies of transgender men during the global crisis: Stressors and coping strategies of transgender men - Srivastava, Akanksha; Arya, Yogesh Kumar; Joshi, Shobhna; Singh, Tushar (Psychology Hub, 2024)
Introduction: The lockdown protocols with various restrictions were put in effect to stop the proliferation of coronavirus. It brought many challenges in the life of mass community, but the challenges faced by transmen during the lockdown were unique and even more challenging which led to the poor psychological and physical health and well-being of these individuals. The present paper aims to understand the subjective ordeal of transmen, the stressors they faced at the time of lockdown and their coping strategies opted to deal with the stressors. Method: Semi-structured interviews were conducted with 15 transmen after the end of lockdown. The interviews were analyzed using Thematic content analysis. Result: The analysis shows several physical, psychological, and social stressors emerged during pandemic including emotional and physical abuse from unaccepting parents, unavailability of supportive organization, inaccessibility of medical assistance and hormone treatment, suicidal ideation due to free time, feeling of isolation and use of wrong pronouns all affecting the mental health severely. To deal with these stressors the transmen adopted various strategies that include, cognitive appraisal, emotional support from friends and self-help thought. Conclusion: Findings are discussed within the Indian context during the pandemic. The findings of present work will help transgender men in suggesting the ways of dealing with the stressors at uncertain times.